Big and Fast: GPS Loggers Reveal Long-Range Movements in a Large, Riverine Turtle - Shashwat Sirsi; Andrew R. MacLaren; Daniel H. Foley; Austin M. A. Bohannon; Jonathan P. Rose; Brian J. Halstead; Michael R. J. Forstner (Conservation)
Rio Grande Cooters (Pseudemys gorzugi) occupy the Rio Grande watershed and have among the smallest ranges of all North American freshwater turtles. Anthropogenic dewatering is considered to have caused range contractions and population declines. We sought to facilitate management recommendations by determining the extent of movement and potential associations with extrinsic cues. We conducted a GPS-enabled telemetry study from August 2015 to May 2017 on the Devils River in Texas, USA. We included Capture–Mark–Recapture data from 2011, 2014, and 2015–2018 to determine population status in conjunction with movement ecology. Turtles showed increased movement as streamflow and water depth increased. Larger movements were also made mid-year, coincident with the peak nesting season. We speculate that seasonality and increases in streamflow facilitate switches from slower, localized movement to transiting modes. We observed individual heterogeneity in transitory movements. Such movements led us to maintain our population estimate of 726 to 1219 individuals is representative of the entire Devils River. The extent of movement in P. gorzugi has been previously underestimated and long-range movements could explain observed genetic structure. Future efforts to re-establish natural flow regimes in the Rio Grande basin could potentially be the most effective management approach for this range-restricted chelonian.